Performance Study of Multilayered Multistage Interconnection Networks under Hotspot Traffic Conditions. (28th December 2010) - Vasiliadis, Dimitris; Rizos, George; Vassilakis, Costas
Abstract : The performance of Multistage Interconnection Networks (MINs) under hotspot traffic, where some percentage of the traffic is targeted at single nodes, which are also called hot spots, is of crucial interest. The prioritizing of packets has already been proposed at previous works as alleviation to the tree saturation problem, leading to a scheme that natively supports 2-class priority traffic. In order to prevent hotspot traffic from degrading uniform traffic we expand previous studies by introducing multilayer Switching Elements (SEs) at last stages in an attempt to balance between MIN performance and cost. In this paper the performance evaluation of dual-priority, double-buffered, multilayer MINs under single hotspot setups is presented and analyzed using simulation experiments. The findings of this paper can be used by MIN designers to optimally configure their networks.